1988
DOI: 10.1002/1098-108x(198809)7:5<589::aid-eat2260070502>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorders in anorexic patients

Abstract: This study was designed to compare personality disorders in restricting and bulimic anorexics. Thirty patients fulfilled DSM‐III criteria for anorexia nervosa and 38 patients fulfilled, in addition, DSM‐III criteria for bulimia. Patients were given Axis I and II, DSM‐III diagnoses. They were administered Gunderson's Diagnostic Interview for Borderlines, the MMPI, and the Childhood Events Questionnaire. We find from these different lines of evidence that both restricter and bulimic anorexics requiring hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
2
4

Year Published

1993
1993
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 13 publications
(6 reference statements)
8
34
2
4
Order By: Relevance
“…To the best of our knowledge, seven studies have examined specifically this issue by the use of interviews and specified diagnostic criteria (Ames-Frankel et al, 1992;Gartner, Marcus, Halmi, & Loranger, 1989;Herzog, Keller, Lavori, Kenny, Sacks, 1992;Piran, Lerner, Garfinkel, Kennedy, & Brouillette, 1988;Powers et al, 1988;Wonderlich, Swift, Slotnick, & Goodman, 1990;Zanarini et al, 1990). For restrictive AN, the rate of a comorbid OCPD ranged from 3.3% (Piran et al, 1988) to 60% (Wonderlich et al, 1990). In the largest study, Herzog, Keller, Lavori, Kenny, and Sacks (1992) found a rate of 10% for restrictive anorectic patients and 4% for bulimic anorectic patients.…”
Section: An and Obsessive Compulsive Personalitymentioning
confidence: 99%
“…To the best of our knowledge, seven studies have examined specifically this issue by the use of interviews and specified diagnostic criteria (Ames-Frankel et al, 1992;Gartner, Marcus, Halmi, & Loranger, 1989;Herzog, Keller, Lavori, Kenny, Sacks, 1992;Piran, Lerner, Garfinkel, Kennedy, & Brouillette, 1988;Powers et al, 1988;Wonderlich, Swift, Slotnick, & Goodman, 1990;Zanarini et al, 1990). For restrictive AN, the rate of a comorbid OCPD ranged from 3.3% (Piran et al, 1988) to 60% (Wonderlich et al, 1990). In the largest study, Herzog, Keller, Lavori, Kenny, and Sacks (1992) found a rate of 10% for restrictive anorectic patients and 4% for bulimic anorectic patients.…”
Section: An and Obsessive Compulsive Personalitymentioning
confidence: 99%
“…In general, personality disorders have been found to be relatively common, but the proportion of affected persons has ranged rather widely. For example, in 13 studies reporting on the full array of DSM-I11 or DSM-111-R Axis I1 diagnoses (Ames-Frankel et al, 1992;Gartner, Marcus, Halmi, & Loranger, 1989;Gwirtsman, Roy-Byrne, Yager, & Gerner, 1983;Herzog, Keller, Lavori, Kenny, & Sacks, 1992;Kennedy, McVey, & Katz, 1990;Levin & Hyler, 1986;Piran, Lerner, Garfinkel, Kennedy, & Brouillette, 1988;Powers, Coovert, Brightwell, & Stevens, 1988;Schmidt & Telch, 1990;Wonderlich, Swift, Slotnick, & Goodman, 1990;Yager, Landsverk, Edelstein, & Hyler, 1989;Yates, Sieleni, Reich, & Brass, 1989;Zanarini et al, 1990), the rate of one or more personality disorders among eating disorder samples has varied from 27-93%. Rates of specific personality disorders have also varied.…”
mentioning
confidence: 99%
“…Por otro lado, las investigaciones que utilizaron entrevistas estructuradas para trastornos de personalidad como son el SCID II (Structured Clinical Interview for DSM) y la PDE (Personality Diagnostic Interview) o para trastornos borderline de la personalidad como la DIB (Diagnostic Interview for Borderlines) encontraron tasas de prevalencia entre un 21 % (Sansone et al, 1989) a un 42 % (Piran et al, 1988). En general, los estudios han demostrado que el trastorno de personalidad borderline se halla presente en una considerable minoría de casos, sin embargo algunos autores como Pope y Hudson (1989) han afirmado que existe un importante solapamiento entre los trastornos borderline y la sintomatología depresiva, presente también en gran cantidad de pacientes.…”
Section: Borderlineunclassified
“…Las tasas de prevalencia varían entre un 25% a un 53% en muestras de pacientes bulímicas de peso normal (Yates, Sieleni, Reich & Brass, 1989;Levin & Hyler, 1986;Wonderlich, Swift, Slotnick & Goodman, 1990;Powers et al, 1988). En el caso de pacientes anorexicas, restrictivas y bulímicas, las tasas de prevalencia disminuyen a un 0% a un 20% (Piran et al 1988;Wonderlich et al, 1990).…”
Section: Histriónicounclassified
See 1 more Smart Citation